Muscle Abnormalities and Meat Quality Consequences in Modern Turkey Hybrids - Zampiga, Marco; Soglia, Francesca; Baldi, Giulia; Petracci, Massimiliano; Strasburg, Gale M.; Sirri, Federico (Frontiers in Physiology, 2020)
Turkey meat is the second most consumed poultry meat worldwide and represents an economic source of high-quality protein for human consumption. To fulfill the increasing demand for turkey meat, breeding companies have been selecting genetic lines with increased growth potential and breast muscle proportion. Moreover, the progressive shift towards further processed products has emphasized the need for higher standards in poultry meat to improve its technological characteristics and functional properties (i.e. water holding capacity). However, as observed for broiler chickens, a growing body of scientific evidence suggests that the intense selection for the above-mentioned traits could be associated with a greater occurrence of growth-related myopathies and abnormalities and, consequently, to increased downgrading rates and overall reduction of meat quality characteristics. In the past, muscle abnormalities such as deep pectoral myopathy, pale-soft-and-exudative (PSE)-like meat, and focal myopathy have been reported in turkey lines selected for increased growth rate. In addition, the presence of white striations in the superficial layer of Pectoralis major muscle, as well as the tendency of muscle fiber bundles to separate resulting in an altered breast muscle structure, have been detected in commercial turkey abattoirs. Furthermore, past investigations revealed the presence of another quality issue depicted by an overall toughening of the breast muscle. These meat abnormalities seem to macroscopically overlap the white-striping, spaghetti-meat and wooden breast conditions observed in pectoral muscle of fast-growing, high breast-yield chicken hybrids, respectively. Considering the high economic impact of these growth-related abnormalities in broilers, there is an increasing interest of the turkey industry in estimating the occurrence and the impact of these meat quality issues also in the modern turkey lines. Studies have been recently conducted to assess the effect of the genotype on the occurrence of these emerging growth-related defects and to evaluate how meat quality properties are affected by white-striping condition in turkeys, respectively. Therefore, this review aims to provide a critical overview of the current understanding regarding the growth-related abnormalities and their impact on meat quality in modern turkey hybrids with the hope that this information may improve the knowledge concerning their overall effect on poultry meat.